A study of the volatile oil extracted from the leaves of Cinnamomum mindanaense Elm (Fam. Lauraceae) - Verano, Ofelia Q.
The volatile oil from the leaves of Cinnamomum mindanaense Elm. (Fam. Lauraceae) was extracted with steam using the Clevenger apparatus for heavier than water distillation. The air dried leaves was found to contain 0.4% of volatile oil.